Sejarah Agama dalam al-Qur’an; Dari Sederhana Menuju Sempurna - Imam Ibnu Hajar (TSAQAFAH, 2014)
Religion does not come at once as can be seen today. Religion comes with the following level of human’s intellectual development and condition. So that, religion is always suitable to human in all ages and times. The process and development of religion can be traced through the history of the religion itself such as Prophet Adam, as to which is perpetuated by the Quran, which is very simple and not with a lot of roles of shari’ah. Shari’ah brought by the prophets are increasingly developed so created religion as brought by Prophet Muhammad which we can see his teachings today. Nevertheless, the Prophets’ struggle in carrying and introducing religion to bring the people to a better life is not simple. The prophets had to fight hard and even risked their life themselves. But they are not an ordinary man. They are an elected man to run the heavy duty. They have the durability and above all suffering far beyond what ordinarily people do. The process of proselytizing of prophets always shows the resilience and tremendous fortitude. Thus the heavy duty that God gave to them can be done well. However, not all of the prophets have the same success. The series of prophets is closed with the advent of Prophet Muhammad with Islam. This paper focuses on how the development of religion until it becomes a perfect religion passing through the prophets in a very long period of time.